The relationship between self-efficacy and organizational citizenship behavior: the mediating role of emotional intelligence in teachers - Annisa Putri; Hasanuddin Hasanuddin; Suryani Hardjo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Organizational Citizenship Behavior (OCB) among teachers plays a crucial role in enhancing the effectiveness of school organizations; however, the level of OCB is still found to be suboptimal. Internal factors such as self-efficacy and emotional intelligence are presumed to contribute to the promotion of such behavior. This study aims to analyze the relationships among self-efficacy, emotional intelligence, and OCB, as well as to examine the mediating role of emotional intelligence. This research employs a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The population consisted of 312 teachers registered in the Basic Education Data (Dapodik) for the 2024/2025 academic year, and all teachers were included as the research sample using a total sampling technique. The research instruments include scales measuring self-efficacy, emotional intelligence, and OCB. The results indicate that self-efficacy has a positive and significant effect on OCB, both directly and indirectly through emotional intelligence. Emotional intelligence is proven to partially mediate this relationship. These findings suggest that improving teachers’ OCB can be achieved through strengthening self-efficacy and developing emotional intelligence. This study contributes to clarifying the psychological mechanisms underlying OCB formation and serves as a basis for developing programs aimed at enhancing teacher quality.